2021
DOI: 10.1093/trstmh/traa179
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and perceived utility of different diagnostic tests and sample types for trachoma surveillance in the Bijagos Islands, Guinea Bissau

Abstract: Background Trachoma is the leading infectious cause of blindness worldwide and is nearing elimination as a public health problem in Guinea Bissau. It is imperative that elimination is followed by a successful postvalidation surveillance programme. The aim of this study was to determine the acceptability and perceived utility of different diagnostic tests and sample types that could be used for postvalidation trachoma surveillance in the Bijagos Islands, Guinea Bissau. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In contrast, refusal to provide a sample was largely driven by mistrust of the sample's purpose and fear about misuse or physical harm to the individual. These results parallel findings from other settings that tie decisions to participate in STH programs, willingness to provide a stool sample for diagnostic purposes, and consent to NTD surveillance activities to an understanding of the importance of the research, fears of how the samples might be misused, and perceived benefits [15][16][17]19]. Similarly, studies examining participation in MDA have found that trust in the program, rumors about harmful consequences, and perceptions of benefits drive acceptability of treatment [29][30][31][32].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 72%
See 1 more Smart Citation
“…In contrast, refusal to provide a sample was largely driven by mistrust of the sample's purpose and fear about misuse or physical harm to the individual. These results parallel findings from other settings that tie decisions to participate in STH programs, willingness to provide a stool sample for diagnostic purposes, and consent to NTD surveillance activities to an understanding of the importance of the research, fears of how the samples might be misused, and perceived benefits [15][16][17]19]. Similarly, studies examining participation in MDA have found that trust in the program, rumors about harmful consequences, and perceptions of benefits drive acceptability of treatment [29][30][31][32].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 72%
“…Evidence from clinical settings in higher income countries indicate that providing stool samples is driven by perceived benefits, clear information about the process, and protocols that assuage fears around hygiene and discretion [ 17 ]. Studies of other NTD surveillance activities, including those for onchocerciasis and trachoma, indicate that less invasive sampling procedures are preferable and decisions are similarly driven by perceived benefits, and trust and understanding of the program [ 18 , 19 ]. However the specific factors influencing participation in STH stool-based surveillance activities are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The community FGD participants highlighted the importance of pre-visit sensitisation, as well as feedback immediately post-examination, in order to improve participation in trachoma grading activities. The importance of good communication with communities has been noted by others 30 —if interventions are being implemented with and by communities, rather than to them, they are much more likely to be successful.…”
Section: Discussionmentioning
confidence: 95%
“…A study in the Bijagós Islands, Guinea Bissau on different diagnostic tests and sample types for trachoma surveillance (including clinical exams, eye swabs, and finger-prick blood samples) reported that although all the studied test types were generally acceptable, there was a preference among community members for laboratory-based testing; these results were considered more accurate than clinical examination. [ 26 ] Additionally, sample types that did not require close proximity to the eye (i.e., finger-prick blood samples) were preferred. [ 26 ] Our study had similar results, with participants noting a perception of improved accuracy from laboratory-based methods, although expressing some unease with the eye swab and blood spot procedures, especially with regards to children.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Additionally, sample types that did not require close proximity to the eye (i.e., finger-prick blood samples) were preferred. [ 26 ] Our study had similar results, with participants noting a perception of improved accuracy from laboratory-based methods, although expressing some unease with the eye swab and blood spot procedures, especially with regards to children. This similarity in findings is reassuring given the different locations and population types, indicating some generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%